The isometric horizontal push test correlates with jumping and sprinting performance among athletes and recreationally active controls - Dello Iacono, A.; Holgado Lopez, C.; Bakhshi, A.; Halperin, I. (Biology of Sport, 2022)
The aim of this study was two-fold: (i) to examine the relationships between force outputs measured in the isometric horizontal push test (IHPT) and athletic performances; (ii) to compare IHPT outputs between football players and recreationally active controls. Thirty-two male subjects (football players, n = 16; university students, n = 16) completed the IHPT, countermovement jump (CMJ), standing long jump (SLJ), 5 m, 10 m and 20 m sprint tests, randomly across two testing sessions. Multivariate linear regression analysis was used to examine the relationships between IHPT outputs and athletic performances by accounting for the subjects` athletic background. An independent sample t-test was used to compare the IHPT outputs between groups. Moderate to very strong linear relationships (r2 range: 0.16-0.56) were found between the IHPT and all athletic performances (all p < .026). Percent variance explained by the IHPT outputs after accounting for groups difference was 16%, 56%, 54%, 48% and 40% for CMJ height, SLJ distance, 5 m, 10 m and 20 m sprint performances, respectively. Compared to controls (6.18 ± 0.89 N/kg), football players (10.09 ± 1.57 N/kg) achieved greater IHPT force outputs (p < .001, Hedges` g = 3.2, large ES). The IHPT is clearly correlated to horizontal and vertical athletic performances and can adequately distinguish between athletes and recreationally active controls based on their IHPT results. Future studies should examine the usefulness of the IHPT as a testing tool informing training prescription and performance monitoring practices.